1992
DOI: 10.1093/oxfordjournals.annonc.a058070
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary plasmacytoma: Clinical behaviour and response to treatment

Abstract: The clinical features and response to treatment of 35 patients (pts) with extramedullary plasmacytoma (EMP) were retrospectively analysed. The median age at diagnosis was 49 years (28-72). Twenty-two pts (63%) had stage I disease (localized to the primary site) 12 of whom (34%) had stage I-E (locally extended). Three pts (9%) had stage II (regional lymph nodes involved) and 10 (29%) stage III (disseminated disease). In locoregional disease (stages I, I-E, II) complete local control was achieved in 22 of 25 pts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
3

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 17 publications
4
60
0
3
Order By: Relevance
“…Corwin and Lindberg (1979) and Mendenhall et al (1980) required less than 10% plasma cells in the bone marrow, while Knowling et al (1983) required normal bone marrow biopsy for the diagnosis of EMP. Soesan et al (1992) has accepted the diagnosis of EMP for those plasma cell tumours which presented in an extramedullary site and did not arise from bone marrow with a breach through the bone cortex. Most authors agree that the detection of a monoclonal band on serum protein electrophoresis or urinary Bence Jones protein does not necessarily preclude the diagnosis.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Corwin and Lindberg (1979) and Mendenhall et al (1980) required less than 10% plasma cells in the bone marrow, while Knowling et al (1983) required normal bone marrow biopsy for the diagnosis of EMP. Soesan et al (1992) has accepted the diagnosis of EMP for those plasma cell tumours which presented in an extramedullary site and did not arise from bone marrow with a breach through the bone cortex. Most authors agree that the detection of a monoclonal band on serum protein electrophoresis or urinary Bence Jones protein does not necessarily preclude the diagnosis.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Subsequent development of a paraprotein may signal a recurrence (Kapadia et al, 1982;Mock et al, 1987). Holland et al (1992) felt that patients with paraprotein at the time of diagnosis fared worst, while Harwood et al (1981), Soesan et al (1992) and Shih et al (1995) suggested no effect on prognosis provided they return to normal after treatment. Only one patient, in our series, had an IgA monoclonal band on serum protein eletrophoresis at diagnosis, and he has remained disease-free.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Soft tissue localized plasmacytoma occurs in 80% of cases in the oral cavity or upper respiratory tract and prognosis is excellent after local treatment only. 7 In our patient, response to local treatment was complete and maintained for over 2 years at the time of writing. Extramedullary relapse without bone marrow infiltration seems to occur more frequently after autologous BMT as compared to conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 50%